Análisis de las figuras literarias de los siete primeros poemas de la obra un perro tocando la lira, de Euler Granda - Ocampo Jiménez, Pedro Javier (2016)
The research entitled: ANALYSIS OF LITERARY FIGURES OF FIRST SEVEN POEMS OF THE WORK A DOG fiddling, EULER GRANDA. He had as general objective: to analyze literary figures of the first seven poems of the aforementioned work. The methods used were: analysis of texts of Lazaro Carreter, applied to poetry, from the perspective of construction of the plot background, methods such as analytic-synthetic was also used, in terms of technique, the literature was used, which allowed collecting the universal theoretical argument which served as the basis for all research. As results were obtained; to identify the following rhetorical figures: anaphora, Anadiplosis, alliteration, epithet, exclamation, hyperbole, metaphor, paradox, pleonasmo, simile, synecdoche, synonyms, allegory, antithesis, enumeration, parallelism, personification, hyperbaton apostrophe. Regarding the comment was obtained as a result the presence of a philosophical background, where I highlight the plot from a stylistic approach that has been applied to harmonize and give aesthetic poems and versification same constituting its verses are free. So it was concluded that the poet uses the rhetorical resources to make a proper and popular style, they show the objective reality of a society in systemic troubles, fuses politics with philosophy constituting its expressions in a beautiful and everyday language through literary devices, so it is advisable to study the works of this writer for his story content.